The United States Motivation in Having Cyber Security Cooperation With China - Purwanti, Devi (Department of International Relations Universitas Pertamina, 2021)
The United States and China had conducted cyber cooperation since 2011. But in 2013, both states were involved in the cyber conflict that made the previous cyber collaboration had been ineffective. After that, in 2015, both states agreed to re-form cyber cooperation. This study aims to analyse the United States' motivation in conducting cyber partnerships with China using the cybersecurity concept. This research has discovered at the national level, the United States tried to achieve its information assurance through cyber defence strategy by strengthening collaboration. On the other hand, at the international level, norm construction through bilateral collaboration has made the United States become an impactful actor in international cybersecurity.